Residue estimation of chlorpyriphos and lambda cyhalothrin in cardamom [Elettaria cardamomum (L.) Maton] - N P Kumar, T George, (Journal of Spices and Aromatic Crops, 2013)
The aim of the study was to validate the method for estimation of residues of chlorpyrifos and lambda cyhalothrin in cardamom. Accordingly, the limit of detection (LOD) arrived at was 0.005 μg kg-1 and the limit of quantitation (LOQ) arrived at was 0.01 mg kg-1. Chlorpyriphos and lambda cyhalothrin residues showed a linear response in the range of 0.005-5.0 μg kg-1 and the mean recovery obtained was 97.3% for chlorpyriphos and 98.9% for lambda cyhalothrin with satisfactory RSD values. The initial residues of chlorpyriphos applied at a concentration of 0.05% in cardamom was 1.6 μg kg-1 and the residue was 5.64 μg kg-1 after processing, with a processing factor of 3.53, while the lambda cyhalothrin when applied at 0.0025% resulted in initial residues of 0.26 μg kg-1 which got magnified to 1.19 μg kg-1, with a processing factor of 4.58. The processing factor obtained in this study led to the conclusion that the residues of chlorpyriphos were magnified 3.53 times and that of lambda cyhalothrin were magnified 4.58 times of initial residues, mainly due to loss of weight of cardamom due to dehydration during curing.